1993
DOI: 10.1002/jsfa.2740620308
|View full text |Cite
|
Sign up to set email alerts
|

Geographical classification of Greek virgin olive oil by non‐parametric multivariate evaluation of fatty acid composition

Abstract: Fatty acid compositional data for Greek virgin olive oils from 24 years of harvest and various regions and cultivars were evaluated using chemometric methods. Non-parametric discriminant analysis after proper transformation of the data seems to be a suitable approach to characterise the oils according to the geographical origin and may produce a scientific basis for the assignment of an 'appellation d'origine' trade mark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 16 publications
3
58
0
2
Order By: Relevance
“…These results are similar to those already described for these cultivars [14][15][16][17][18] The variations in fatty acid content observed in olive oil samples obtained from both cultivars were probably related to both genetic factors and environmental conditions during fruit development and maturity [19]. Some authors have used the total fatty acid composition to differentiate olive oils according to the geographical area of production for oils from Greece [20] and Italy [21].…”
Section: Fatty Acid Compositionsupporting
confidence: 88%
“…These results are similar to those already described for these cultivars [14][15][16][17][18] The variations in fatty acid content observed in olive oil samples obtained from both cultivars were probably related to both genetic factors and environmental conditions during fruit development and maturity [19]. Some authors have used the total fatty acid composition to differentiate olive oils according to the geographical area of production for oils from Greece [20] and Italy [21].…”
Section: Fatty Acid Compositionsupporting
confidence: 88%
“…Some of them reported that the fatty acid composition of olive oil depends primarily on the cultivar (Uceda et al, 1999;Ayton et al, 2001), suggesting that fatty acid composition could be used for discriminating between cultivars by chemometric methods (Perri et al, 1999). However, a great influence of environmental factors such as year of harvest, location, season or climatic conditions (in particular the temperature and rainfall during fruit growth and ripening) on the variation of some fatty acids has also been reported (Tsimidou and Karakostas, 1993;Panelli et al, 1994;Tous and Romero, 1994;Tovar et al, 2002). Moreover, it has been previously reported in other olive breeding programs that the evaluation of olive progenies is rather complex and some characters like oil content seem to stabilize only after 2-3 years (Lavee, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relationship between the intake of olive oil, the richest dietary source of monounsaturated fatty acid and breast cancer risk and progression is a current issue of discussion . It is well established by many authors that the fatty acid composition of olive oil is strongly influenced by cultivar (Tsimidou et al, 1993;Zarrouk et al, 2008), the maturation stage of fruit (Synouri et al, 1995) and the zone of origin GRASAS Y ACEITES, 60 (5), OCTUBRE-DICIEMBRE, 498-506, 2009 (Ranalli et al, 1997). Nevertheless, a varietal parameter seems to be the most important and determining factor.…”
Section: Introductionmentioning
confidence: 99%